Pengaruh Bauran Pemasaran Jasa terhadap Keputusan Konsumen pada Hotel Bintang Dua di Kota Palembang - Bassi, Aliming (Universitas muhammadiyah palembang, 2014)
This watchfilness internal issue is influence either through together also partially marketing mix towards consumer decision at two star hotel in Palembang City. This watchfulness is the aim to detect influence eitherthrough together also partially product, price, place, promotion, people, physical evidence towards consumer decision at two star hotel in Palembang City. Based on level explanation this watchfulness is watchfulness asosiatif.Variables used are six independent variables that is product, price, place, promotion, people, physical evidence and one dependent variable, consumer decision as a whole developed to be 49 indicators. Found 270 two star hotel consumer that taken as watchfulness sample based on clustersampling. Primary data is got by using distribution technique questioner. Analysis technique taht used path analysis.Analysis result in through together show product, price, place, promotion, people, physical evidence has influence significant according to together towards consumer decision at two star hotel in Palembang city. Analysis results in partially according towards consumer decision, price not influentialsignificant.